Передатні функції та частотні характеристики теплових об’єктів типу циліндричної стінки - Кубрак, А. І.; Жученко, О. А. (НТУ "ХПІ", 2014)
Представлені передатні функції та частотні характеристики циліндричної теплоакумулюючої стінки як об’єкта з розподіленими параметрами у залежності від граничних умов на зовнішній і внутрішній поверхнях. Було запропоновано кілька нетривіальних способів для розрахунку частотних характеристик циліндричних теплоакумулюючих стінок. Отримані результати можуть бути використані при синтезі систем керування

From mathematical modeling point of view a lot of plants in different industries can be considered as cylindrical heat storage walls with distributed parameters. The aim of this study was to receive transfer functions and frequency responses as mathematical models of above mentioned plants. To solve this problem the main equation of heat conductivity was put in basis. In addition three kinds of boundary conditions on external and internal wall surfaces were taken into account. Different combinations of boundary conditions on external and internal wall surfaces result in different kinds of transfer functions and frequency responses. These functions are transcendental and perhaps must be simplified for practical using. It was proposed few nontrivial ways in order to calculate frequency responses of cylindrical heat storage walls. Obtained results can be used for researching of plants, which can be considered as cylindrical heat storage walls with distributed parameters, and for control system synthesis
Transfer functions and frequency responses of thermal objects cylindrical wall type
Keywords: теплоакумулююча стінка; граничні умови; математичне моделювання; інтегральні рівняння; transfer function; frequency response; cylindrical heat storage wall; boundary conditions